Health and Productivity Benefits with Early Intensified Treatment in Patients with Type 2 Diabetes: Results from Korea - Foteini Tsotra MPH; Ankur Malhotra MD; Platon Peristeris PhD; Ioannis Athanasiou MSc; Malina Müller PhD; Giovanni Bader MD, PhD (SAGE Publishing, 2024)
The available evidence suggests positive health outcomes associated with early treatment intensification in Type 2 diabetes mellitus (T2DM). Our study estimated the productivity effects arising from improved health correlated with early intensified treatment in T2DM in Korea. Using a recently published methodology and model, we investigated the association between early intensified treatment and the probability of experiencing fewer diabetes-related complication events. Treatment strategies leading to better health outcomes are expected to be associated with social value through increased participation in paid and unpaid work activities. Therefore, we translated the lower incidence of complications into monetary terms related to productivity for the Korean population. We quantified productivity by considering (a) absenteeism, (b) presenteeism, (c) permanent loss of labor force, and (d) activity restriction. Deterministic and probabilistic sensitivity analyses in the base case parameter were performed. Approximately, 1.7 thousand (standard deviation [SD] ±580 events) micro- and macrovascular complication events could potentially be avoided by early treatment intensification. This led to a societal gain attributed to increased productivity of 23 million USD (SD ± $8.2 million). This article demonstrates the likelihood of achieving better health and productivity through early intensified treatment in diabetes.